A CONTRASTIVE ANALYSIS OF ARABIC AND ENGLISH AFFIXATION - Astutik, Lidia; Andayani, Sri; Sutrisno, Adi; Tjahyadi, Indra (JURNAL LITERASI, 2024)
This research comparative between Arabic and English affixation. This research was raised because of the assumption that when students have learned and know about one of the two languages, the students assume that the other language is difficult to understand. This research has two main objectives there are to find the differences and similarities of Arabic and English affixation. The method used in this research is descriptive qualitative. This method is employed to describe the analysis and findings, which focus on analyzing comparative between Arabic and English affixation. The data analysis mehod this research uses Metode Agih (distributional method). Metode Agih (distributional method) is a method whose determining tool is precisely part of the languge concerned, namely Arabic and English. This research gets the result, There are six differences of Arabic and English in affixation In Arabic, the addition of verbs to nouns has three affixes, namely prefix, infix and confix. While English according to katamba theory, the addition of verbs to nouns only has suffixes. The similarities there are three, In general both languages have affixed words. Both language have additional letters and meaning changes. While specifically Arabic and English can changed from verb into noun.